Itqan al-Muluk bi Ta’dil as-Suluk: The Implication of Terengganu Institution 1911 Promulgation - Abd Wahab, Norazilawati; Sulaiman @ Abd. Rahim, Ruzaini; Mohd Noor, Arba’iyah; Abdullah, Mohd Firdaus; Mohamed Hassan, Noraini (Journal of Al-Tamaddun, 2022)
The concern felt by Sultan Zainal Abidin III (1881-1918) (“the Sultan”) over the entry of a British agent in Terengganu pursuant to the agreement entered into between Terengganu and Great Britain on 22 April 1910 had led to the enactment of Itqân al-Mulûk bi Ta’dîl Al-sulûk, or the Law for the Self-Government of Terengganu, on 2 November 1911. The Sultan attempted to protect Terengganu from foreign interference despite having to abide by the terms of the said agreement, which required a British agent to be stationed in Terengganu. The establishment of the said law appears to be an attempt to maintain the dominance of the local government in Terengganu’s governmental system, and this move also affected its socio-economic development throughout the stated period. The interesting element about this law is the presence of a very strong Islamic influence, which shows that the Sultan strictly adhered to the teachings of Islam during his reign in Terengganu. This study aimed to analyse the extent to which the presence of British agents in Terengganu had influenced the actions and thinking of Sultan Zainal Abidin III in enacting and establishing Itqân al-Mulûk bi Ta’dîl Al-sulûk. It also aimed to examine how far Itqân al-Mulûk bi Ta’dîl Al-sulûk played a role in empowering the political and socio-economic sectors in Terengganu during the specified period and the extent to which the teachings of Islam embedded within it were used to protect and preserve the sovereignty of Terengganu against British intervention at the time. This research adopted a qualitative method that involved the collection and analysis of data from primary sources obtained from the Terengganu State Museum and the National Archives of Malaysia, such as the Manuscript of Itqân al-Mulûk bi Ta’dîl Al-sulûk, CO 840/1 (Terengganu Administration Report, 1910-1930), CO 840/2 (Terengganu Administration Report 1931-1940), The Terengganu Secretary of State File, and the Terengganu British Advisor File. In addition, secondary sources such as journals, books, chapters of books, and magazines were also used to further reinforce the study conducted. The findings proved that the enactment of Itqân al-Mulûk bi Ta’dîl Al-sulûk managed to fortify the political system in Terengganu, which projected a very strong image of Islam. In fact, it is this strengthening of the political system which led to the development of the economy, due to the availability of stable sources of income for the Malay farmers and female entrepreneurs at the time.